The Influence of Self-Efficacy and Social Support on Academic Resilience in Students of the Faculty of Teacher Training and Education Sebelas Maret University - Dyah Ayu Syafinah; Dini Octoria (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2025)
This study aims to determine: (1) The effect of self-efficacy on academic resilience in FKIP UNS students (2) The effect of social support on academic resilience in FKIP UNS students (3) The effect of self-efficacy and social support on academic resilience in FKIP UNS students. The research approach used is quantitative descriptive. A sample of 377 students was selected from a population of 6.738 FKIP UNS students through simple random sampling technique. Data were collected using a questionnaire, and analyzed using descriptive statistical analysis and hypothesis testing in the form of t-test and f-test. The results prove that self-efficacy and social support have a positive and significant effect on academic resilience in FKIP UNS students partially and simultaneously. Keywords: Self Efficacy, Social Support, Academic Resilience